Respirator fit of a medium mask on a group of South Africans: a cross-sectional study - Wilson Kerry S; Spies Adri; Ferrie Robert (BMC, 2011)
Abstract Background In South Africa, respiratory protective equipment is often the primary control method used to protect workers. This preliminary study investigated how well a common disposable P2 respirator fitted persons with a range of facial dimensions. Methods Quantitative respirator fit tests were performed on 29 volunteers from different racial, gender and face size groups. Two facial dimensions width (bizygomatic) and length (menton-sellion) were measured for all participants. Results In this study 13.8% of the participants demonstrated a successful fit with the medium sized mask. These included participants from three different racial and both gender groups. The large percentage of failed fit tests (86%) indicates that reliance on off-the-shelf respirators could be problematic in South Africa. Conclusions The limitations of this preliminary study notwithstanding, respirator fit appear to be associated with individual facial characteristics and are not specific to racial/ethnic or gender characteristics.